Spinning Induced Compression Strength of Precast Hollow Concrete Piles - Gogot Setyo Budi; Suseno P.K.; Winata S.K. (Civil Engineering Dimension, 2017)
Prefabricated precast-hollow concrete pile is widely used as deep foundations due to its several benefits such as the uniformity in concrete quality and its durability. It is also called spun pile since the spinning method is utilized to compact the fresh concrete. During spinning, the fresh concrete is propelled outward due to centrifugal force, which generates a compaction process and develops a hollow in the center of the pile. Several factors, such as the rate of spinning, frequency, and duration of spinning, are affecting the quality of the pile. This paper presents the study of density and compressive strength of spun piles. The specimens were cored from the spun piles with diameter of 800 mm. The results show that the density and the compressive strength of the concrete at outer region of the spun pile are bigger than those at the inner side.